Vocational Education: Relevance and Reality - Khandpur, Nimrat KD (Voices of Teachers and Teacher Educators, 2019)
The scenario of vacationalisation in India dates back to the colonial period. After independence many of the committees and commissions suggested and endorsed vocationalisation in different forms. The present article focuses on providing a status quo of vocational education in India with a special mention to the National Skill Qualifications Framework (NSQF) and its proceedings the mention of some cases of states like Haryana and Himachal Pradesh strengthens the plan of implementation of NSQF in the country.